PROTECTION OF CHILD VICTIMS OF VIOLENCE IN THE FAMILY FROM THE PERSPECTIVE OF ISLAMIC FAMILY LAW AND POSITIVE LAW (Case Study at the Subang District Attorney‘s Office, West Java Province) - Nurman Akhmadi (UIN Siber Syekh Nurjati Cirebon, 2024)
Cases of violence against children still occur frequently; tragically, in many cases of violence against children, the perpetrators most often come from the familyenvironment or the environment where the child is. The purpose of this study isfirst to explore the occurrence of violence against children in the family, second toexamine more deeply the legal protection of child victims of violence in the familybased on Islamic Family Law and Positive Law at the Subang District Attorney‘sOffice, and third to examine more deeply the development of handling childvictims of violence in the family based on Islamic Family Law and Positive Law atthe Subang District Attorney‘s Office. The research method used by the author isqualitative, where this research is descriptive and tends to use analysis and theory as a guide so that the study focuses on the facts in the field. The type of research used is field research. The research approach used is descriptive. The conclusions obtained are: First, the factors that cause violence against children in the family are two things, namely internal factors, including economic factors; factors that are not biological children, educational factors; external factors, including factors of the child‘s behavior, and social, environmental factors. Second, Islam strictly prohibits acts of violence, especially in educating and caring for children. However, this prohibition does not apply in terms of ubūdiyyah or tarbiyyatuddinniyyah. Child protection, according to positive law, is divided into two, namely, Preventive legal protection and Repressive legal protection. Third, Development in child maintenance, namely parenting, maintaining children, and educating children. The development of handling child abuse in the family at the Subang District Attorney‘s Office is to provide maximum protection to children and their rights, namely providing legal sanctions for the perpetrators of criminal acts so that they do not continue their criminal acts as well as giving a fear effect on others so as not to commit the same criminal acts by paying fines that must be given to victims or restitution.